Determinação da atividade antitumoral de complexos de cobre (II) associado com fenantrolina e aminoácidos - RODRIGUES, Wanderson Barros (2021)
Cancer is a group of multifactorial diseases arising from genetic mutations caused by chemical substances, viral infections, radiation exposure, inflammatory diseases resulting from infection, autoimmune diseases or inherited from the progenitor line. Although platinum-based organometallic complexes are used as first-line drugs in the fight against cancer, they cause a number of problems as serious side effects, including nephrotoxicity, neurotoxicity and ototoxicity. In this sense, new studies with copper-based metal complexes appear, they present a lower toxicity, a greater spectrum of action and can be effective against tumors resistant to the standard treatment with cisplatin. Thus, this work evaluated the antitumor activity in vitro of organometallic complexes of Phenanthroline associated with copper (II) and amino acids, their interaction with DNA molecules in silico and predict their pharmacokinetic properties from in silico studies. Human cancer cell lines HL- 60, PC-3 and SNB-19 and the non-tumor line RAW 264.7 (murine macrophage) were used. Cytotoxicity was assessed using the MTT assay after 72-hour exposure of the cells to the CuPhG and CuPhS complexes. Then, molecular Docking was performed to observe the affinity with the possible target. Finally, the prediction of the pharmacokinetic parameters of copper (II) complexes was carried out, including physical-chemical parameters, pharmacokinetic profile (ADME) and toxicity. The cytotoxicity evaluated by the MTT reduction method showed that the CuPhG and CuPhS complexes showed cytotoxic activity for all strains evaluated. The results of molecular docking of the CuPhG and CuPhS ligands show that the complexes are interspersed with the DNA grooves and have good molecular affinity with the targets. In addition, the pharmacokinetic prediction indicates that complexes have advantageous properties such as less interaction with Cytochrome P450 and P glycoproteins. Both complexes were shown to have antitumor activity, however the CuPhS complex was more selective for tumor cells when compared to the CuPhG complex.